Post Chemotherapy Bone Marrow Recovery in Acute Leukaemias- Comparison of Immature Reticulocyte Fraction with Absolute Neutrophil Count - Humaira Rehman, Lubna Zafar, Madeeha Rehan, Sehar Khalique, Tanzeel Imran (Journal of Rawalpindi Medical College, 2015)
Background : To compare Immature Reticulocyte Fraction IRF) with Absolute Neutrophil Count (ANC) in post chemotherapy acute leukameia patients to assess marrow recovery. Methods: In this comparative study, 45 diagnosed cases of AML and ALL on chemotherapy for remission induction/consolidation, between age group of 2 - 60 years were included. Complete blood count (CBC) was done. Immature reticulocyte fraction was done by using automated hematology analyzer Sysmex XT 2000i.Absolute neutrophil count was calculated from total leukocyte count and differential count of white blood cells. True positive and true negative patients, showing recovery on the basis of IRF and ANC were calculated. Ch- square test was used. P-value <0.05 was considered statistically significant Results: Age ranged from3-39years while the mean age was 15 ± 11 years . Nineteen (42%) patients were male and 26 (58%) patients were female. The mean recovery day for IRF was 11.7± 7.1, while that for ANC was 17.5 ± 9.32.Out of 45 patients, IRF predicted recovery in 41 patients and was unable to show recovery in 4 patients. Similarly ANC predicted recovery in 36 patients, but was unable to predict recovery in 9 patients. In 34 patients, both ANC and IRF showed recovery. So the True positive patients were 34 (75%). In these 34 patients, IRF was early predictor in 24 (70.5%) cases and ANC in 10 (29.5%) cases. Similarly patients who had not shown recovery both by IRF and ANC were 4.So the True negative patients were 4(8.8%). Patients who were negative on IRF were 4. Similarly total patients positive on ANC were 36 and patients who were negative on ANC were 9. Patients showing recovery both by IRF and ANC were 34 out of 45. Conclusion: IRF can predict bone marrow recovery earlier than ANC count .IRF can serve as an additional parameter in patients who are in need of evaluation of bone marrow recovery after chemotherapy.